Innovation and sustainability of micro businesses in Sidenreng Rappang Regency - Zainal, Henni (Universitas Negeri Makassar, 2025)
This study aims to analyze innovation and sustainability ofmicro-enterprises in Sidenreng Rappang (Sidrap) Regency as one of the local economic centers in South Sulawesi. The main focus of the study is to understand how micro-entrepreneurs implement innovation in products, services, and business processes to increase competitiveness, whilemaintaining business sustainability amidst global economic challenges and changes in the businessenvironment. The research method used is a mixed-method approach, with data collection through surveys, in-depth interviews, and direct observation of micro-enterprises in the trade, agriculture, and local craft sectors. The results of the study show that technology-basedinnovation, such as the use of digital media for marketing, and product diversification, play a significant role in driving the growth of micro-enterprises. However, challenges such as limited access to capital, low digital literacy, and lack of infrastructure support are still majorobstacles. To support the sustainability of micro-enterprises, collaboration is needed between localgovernments, local communities, and the private sector in providing training, mentoring, and more inclusive accessto financing. This study concludes that innovationsupported by a conducive business ecosystem can increasethe sustainability of micro-enterprises in Sidrap Regency, while strengthening their contribution to regional economic development. Recommendations are given forstrengthening policies based on economic inclusion anddigitalization of micro-enterprises.Keywords: Innovation, sustainability, micro-enterprises, digitalization, local economy.